SEM-EDS Analysis of Late Helladic Pottery From Koukonisi – Lemnos - Duygu, Ertemin (Πανεπιστήμιο Πελοποννήσου, 2019)
Twenty Late Helladic pottery samples from the site of Koukonisi which is situated on the northeastern of the Aegean Sea is analyzed through SEM-EDS to identify the technological characteristics. These samples were specifically chosen from a larger assemblage comprised of 77 samples which is chemically grouped by NAA analysis by Hein and Kilikoglou (2016). SEM-EDS analysis on the smaller set of samples (twenty) from the larger assemblage (77) is conducted at the National Center of Scientific Research at Demokritos in Athens. Microstructure and surface treatments are identified through backscattered and secondary electron modes while elemental compositions of the ceramic bodies and the surface slips are identified by EDS. At least three measurements were taken from the bodies and surfaces for each samples. These measurements were compared and four technological patterns identified according to red slipped surface decorations. Thanks to SEM-EDS analysis, different microstructures and surface treatments were observed. According CaO content in the ceramic bodies, microstructural characteristics and the color of the ceramic bodies and surfaces, firing structures and atmospheres are assigned to the samples. According to these general results and the vitrification levels of the samples, possible maximum firing temperatures are proposed. Technological patterns observed from the data were compared with the chemical groupings of the samples and possible characteristics were attributed to some samples as local and imported. In general, samples from Koukonisi indicated Mycenaean pottery production characteristics while pottery assigned as local to Koukonisi showed different technological attributes.
Keywords: Κεραμική -- Ανάλυση; SEM-EDS Ανάλυση; Αρχαιότητες -- Ανάλυση; Κεραμική, Αρχαία-- Ελλάδα -- Λήμνος; Λήμνος (Ελλάδα) – Αρχαιότητες; Κεραμική; Ανάλυση; Αρχαιότητες; Κουκονήσι; Λήμνος; SEM-EDS Ανάλυση